Dysregulation of the Fas/FasL system in an experimental animal model of HELLP Syndrome - Gibbens, Jacob (Pregnancy Hypertens, 2017)
INTRODUCTION: Placental FasL is up-regulated in women with HELLP (hemolysis elevated liver enzyme and low platelet) syndrome and has been proposed to contribute to the liver damage seen in these patients. OBJECTIVE: This study aimed to determine if an experimental rodent model of HELLP also had dysregulation of Fas/FasL compared to normal pregnant (NP) rats. We also set out to determine if blockade of the endothelin system regulated Fas/FasL expression in HELLP rats. STUDY DESIGN: On gestational day (GD) 12, sEng (7ug/kg) and sFlt-1 (4.7ug/kg) infusion began via mini-osmotic pump into NP rats. On GD19 plasma and tissue were collected and FasL and Fas were measured via enzyme linked immunosorbent assay and gene expression via real-time PCR. RESULTS: HELLP rats had significantly more circulating and placental FasL compared to NP rats, whereas hepatic FasL was decreased and placental Fas was increased compared to NP rats. Administration of an endothelin A receptor antagonist (ET(A)) beginning on GD12 significantly decreased placental expression of Fas in HELLP rats. Liver mRNA transcript of Fas was significantly increased in HELLP rats compared to NP rats). CONCLUSION: These data suggest that rats in this experimental model of HELLP syndrome have abnormal expression of the Fas/FasL system. Future studies will examine the sources of Fas/FasL dysregulation in this model and if blockade could reduce some of the inflammation and hypertension associated with HELLP syndrome.